Strategic adjustment and the rise of China power and politics in East Asia - Ross, Robert S. 1954-; Tunsjo, Oystein (Cornell studies in security affairs, 2017)
'Strategic Adjustment and the Rise of China' demonstrates how structural and domestic variables influence how East Asian states adjust their strategy in light of the rise of China, including how China manages its own emerging role as a regional great power